"I Know You Think I'm Crazy": Post-Horrorcore Rap Approaches to Disability, Violence, and Psychotherapy - Mikko O. Koivisto (Disability Studies Quarterly, 2018)
Cultural representations of Black people as well as people with mental disabilities have historically been derogatory and dehumanizing. Even though the erroneousness and injuriousness of this representational vilification has been increasingly addressed and acknowledged, the power the imagery possesses seems almost indestructible: the stereotypes and myths about blackness and madness live on persistently in our everyday language, in entertainment, media, and other cultural texts. In the face of its seeming indestructibility, alternative ways can be established for encountering the imagery in ways that employ the inertia of its power. This paper explores first-person representations of mental disability as potential egresses from hegemonic representations of psychiatric disability. Recently some disability studies scholars have explored the relationship between disability and rap music and my work contributes to the discussion by examining the work by the rapper Tyler, the Creator. His first three albums are framed as meetings between the artist and his fictional therapist, who is portrayed by the artist himself. This dialogue/monologue brings forth multiple subject positions that frequently overlap and even collide. Operating on the threshold between performance and representation, and between the autobiographical and the fictional, Tyler, the Creator's œuvre challenges stereotypical representations of both Black men and people with psychiatric disabilities.